Contrasting archaeal and bacterial community assembly processes and the importance of rare taxa along a depth gradient in shallow coastal sediments - Gong, Xianzhe (2023)
Marine microbial communities assemble along a sediment depth gradient and are responsible for processing organic matter. Composition of the microbial community along the depth is affected by various biotic and abiotic factors, e.g., the change of redox gradient, the availability of organic matter, and the interactions of different taxa. The community structure is also subjected to some random changes caused by stochastic processes of birth, death, immigration and emigration. However, the high-resolution shifts of microbial community and mechanisms of the vertical assembly processes in marine sediments remain poorly described. Archaeal and bacterial communities were analyzed based on 16S rRNA gene amplicon sequencing and metagenomes in the Bohai Sea sediment samples. The archaeal community was dominated by Thaumarchaeota with increased alpha diversity along depth. Proteobacteria was the dominant bacterial group with decreased alpha diversity as depth increased. Sampling sites and depths collectively affected the beta-diversity for both archaeal and bacterial communities. The dominant mechanism determining archaeal community assembly was determinism, which was mostly contributed by homogeneous selection, i.e., consistent selection pressures in different locations or depths. In contrast, bacterial community assembly was dominated by stochasticity. Co-occurrence networks among different taxa and key functional genes revealed a tight community with low modularity in the bottom sediment, and disproportionately more interactions among low abundant ASVs. This suggests a significant contribution to community stabilization by rare taxa, and suggests that the bottom layer, rather than surface sediments may represent a hotspot for benthic microbial interactions.